Environmental duodenitis and gastritis, distribution of Campylobacter piloris and relationship with intragastric pH and nitrite (Colombia Medica, 1989)
Relationships between measurements of gastric juice pH, nitrite in the gastric juice, and mucosal colonization by Campylobacter pyloris in dyspeptic patients in a Colombian population exposed to very high rates of gastric cancer were investigated. At the Departmental Hospital of Pasto, Nariño, 62 patients suffering from dyspepsia were assessed. Gastric and duodenal mucosa biopsy specimens from all of them were examined histologically, looking for C. pyloris. Fasting gastric juice samples aspirated at the start of endoscopy were also available for estimation of pH and nitrite. C. pyloris was found in 85.5% of patients with gastritis and 69.2% of people with active duodenitis. An increase in pH in gastric juice was observed when atrophic gastritis was present. Intestinal metaplasic changes were associated with nitrite in the gastric juice. C. pylori is an adjuvant, but it is not necessarily considered as the cause of environmental chronic gastritis.